Attributions for sexual orientation vs. stereotypes: how beliefs about value violations account for attribution effects on anti‐gay discrimination. Issue 4 (26th January 2014) - Reyna, Christine; Wetherell, Geoffrey; Yantis, Caitlyn; Brandt, Mark J.
Abstract Attributions for sexual orientation strongly predict opposition to gay rights policies; however, we propose that beliefs that gays and lesbians violate important values drive gay rights opposition and account for the relationship between attributions and anti‐gay discrimination. In two studies, we found that beliefs that gays and lesbians violate values accounted for much of the relationship between attributions and anti‐gay discrimination. In addition, these stereotypes were the most powerful predictors of opposition to gay rights when both value violations and attributions were included in the model. Results also demonstrated that violations of specific values predicted opposition to policies relevant to those values. This suggests that attributions of choice over sexual orientation are less relevant for predicting opposition to gay rights than beliefs about choice to uphold or violate values.